Sustainability of industry clusters : new member creation in Motorsport Valle - Filsner, G. (Cranfield University, 2007)
The emphasis in cluster theory has been in explaining how and why clustering might contribute to competitive advantage for co-located firms, and hence for the economy. While firms may be encouraged to co-locate to gain from transactional, institutional and knowledge benefits, threats to economic sustainability have been associated with a deterioration of advantages and a failure to adapt, resulting in a decline of competitiveness. This thesis reconsiders industry clusters as organisational populations, suggesting a mechanism through which the population and the resource environment can adapt and survive Cluster sustainability is described as a evolutionary process in which the population and resources of the cluster adapt through the creation of new member firms. Based on an embedded case study of eight firm formation events taking place in the UK motorsport industry, the research examines how an industry cluster regenerates and reproduces itself. The concentration, complexity, and diversity of supply and demand comprising the cluster’s organisational population generate a resource environment which generates creation of new members compatible with the cluster’s knowledge architecture. New member entry depends on the absorptive capacity of the cluster, while contributing to the ability to identify, diffuse and exploit new knowledge. Sustainability of industry clusters is associated with the characteristics that support new member creation.